IMPLEMENTASI PROGRAM KAMPUS MENGAJAR DI SMP NEGERI 47 MAKASSAR - Muhammad Sudirman; Bakhtiar Bakhtiar; Fira Yunita (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2023)
Abstract. This study aims to determine, (1) the implementation of the teaching campus student work program at SMP Negeri 47 Makassar, (2) the inhibiting and supporting factors that influence the implementation of the teaching campus student work program, (3) the benefits of the teaching campus program. Data collection techniques through interviews and documentation. Data obtained through interviews. Together with 7 students, the principal, 1 student section, and 1 staff, and 7 teachers. Data was also obtained from student final reports. The data obtained from the research were then collected and processed by qualitative data analysis.The research results show that. (1) The implementation of the student work program begins with making observations to find out what the situation and school environment are like and then students discuss with their team mates with DPL to discuss what work programs are appropriate and needed at school. Then the work program is conveyed through the school communication forum. All work programs that have been created aim to improve literacy and numeracy, technology adaptation, and school administration assistance. (2) Factors supporting the implementation of the teaching campus student work program are with the help and support from the school and students, teamwork, and book donations, the inhibiting factors for campus students teaching batch 3 are insufficient time estimates, few human resources , and lack of funds. Whereas the things that hinder campus students from teaching batch 4 are inadequate facilities or infrastructure such as the absence of laboratories and microscopes, and the lack of support and appreciation from the school on several matters. In addition, another obstacle is the lack of interest and motivation in learning students at the beginning of the assignment. (3) The benefit of the teaching campus program is tohone the spirit of leadership and students' sense of responsibility. In addition to sharpening the spirit of leadership, students also get benefits in the form of soft skills such as public speaking, critical thinking, problem solving. Experience in helping improve the quality of education through the learning process is also gained by students by collaborating with teachers in creating creative and innovative learning processes. In addition to teaching campus students, teaching can also provide benefits for students, in this case so that students get inspiration and motivation to learn. Then for schools it is hoped that there will be an increase in the effectiveness of the learning process in schools, including in an emergency condition of the Covid-19 pandemic.Keywords: Implementation, teaching campus program, student work programAbstrak.Penelitian ini bertujuan untuk mengetahui, (1) pelaksanaan program kerja mahasiswa kampus mengajar di SMP Negeri 47 Makassar, (2) faktor penghambat dan pendukung yang mempengaruhi pelaksanaan program kerja mahasiswa kampus mengajar, (3) manfaat program kampus mengajar. Teknik pengumpulan data melalui wawancara dan dokumentasi.Data yang diperoleh melalui wawancara. Bersama 7 orang mahasiswa, kepala sekolah, 1 orang bagian kesiswaan, dan 1 orang staf, dan 7 orang guru. Data juga diperoleh dari laporan akhir mahasiswa.Data yang diperoleh dari penelitian kemudian dikumpulkan dan diolah dengan analisis data secara kualitatif.Hasil penelitian menunjukkan bahwa. (1) Pelaksanaan program kerja mahasiswa diawali dengan melakukan observasi untuk mengetahui seperti apa keadaan dan lingkungan sekolah kemudian mahasiswa berdiskusi dengan rekan satu tim bersama DPL untuk membahas program kerja apa yang tepat dan dibutuhkan di sekolah. Kemudian program kerja tersebut disampaikan melalui forum komunikasi sekolah. Semua program kerja yang telah dibuat bertujuan untuk meningkatkan literasi dan numerasi, adaptasi teknologi, dan bantuan administrasi sekolah. (2) Faktor pendukung pelaksanaan program kerja mahasiswa kampus mengajar adalah dengan adanya bantuan dan dukungan dari pihak sekolah serta peserta didik, kerja sama tim, dan donasi buku, faktor penghambat mahasiswa kampus mengajar angkatan 3 adalah estimasi waktu yang kurang, sumber daya manusia yang sedikit, dan kekurangan dana. Sedangkan hal yang menghambat mahasiswa kampus mengajar angkatan 4 adalah fasilitas atau sarana dan prasarana yang kurang memadahi seperti tidak adanya labolatorium dan mikroskop, dan kurangnya dukungan dan apresiasi dari pihak sekolah pada beberapa hal.Selain itu, hambatan lainnya adalah kurangnya minat dan motivasi belajar peserta didik pada awal penugasan. (3) Manfaat program kampus mengajar, adalah mengasah jiwa kepemimpinan mahasiswa. Selain mengasah jiawa kepemimpinan juga mendapatkan manfaat dalam bentuk Soft skillsdidapatkan mahasiswa seperti Public speaking, critical thinking, problem solving.Pengalaman dalam membantu meningkatkan kualitas pendidikan melalui proses pembelajaran juga didaptkan oleh mahasiswa dengan berkolaborasi dengan guru dalam menciptakan proses pembelajaran yang kreatif dan inovatif. Selain bagi mahasiswa program kampus mengajar juga dapat memberi manfaat bagi peserta didik, dalam hal ini agar peserta didik mendapatkan inspirasi dan motivasi belajar. Kemudian bagi sekolah diharapkan terjadi peningkatan efektivitas proses pembelajaran di sekolah termasuk dalam kondisi darurat pandemic covid-19.Kata kunci: Implementasi, program kampus mengajar, program kerja mahasiswa